Verb Errors in Student’s Composition - Nitami, Nila (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2017)
The purpose of this paper is to find out about the frequency of student verb errors, the most frequent errors, and did those errors affects the intelligibility of their composition. The subject of this paper is some of the 6th semester students. The finding later shows the frequency of their errors, the most frequent errors, and their errors caused by incomplete application of rules did affect their intelligibility in writing composition.